Deep Soil Water-Use Determines the Yield Benefit of Long-Cycle Wheat - Flohr, Bonnie M.; Hunt, James R.; Kirkegaard, John A.; Rheinheimer, Brad; Swan, Tony; Goward, Laura; Evans, John R.; Bullock, Melanie (Frontiers in Plant Science, 2020)
Wheat production in southern Australia is reliant on autumn (April-May) rainfall to germinate seeds and allow timely establishment. Reliance on autumn rainfall can be removed by sowing earlier than currently practiced and using late summer and early autumn rainfall to establish crops, but this requires slower developing cultivars to match life-cycle to seasonal conditions. While slow-developing wheat cultivars sown early in the sowing window (long-cycle), have in some cases increased yield in comparison to the more commonly grown fast-developing cultivars sown later (short-cycle), the yield response is variable between environments. In irrigated wheat in the sub-tropics, the variable response has been linked to ability to withstand water stress, but the mechanism behind this is unknown. We compared short- versus long-cycle cultivars × time of sowing combinations over four seasons (2011, 2012, 2015, 2016) at Temora, NSW. Two seasons (2011 and 2012) had above average summer fallow (December-March) rain, and two seasons had below average summer fallow rain (2015 and 2016). Initial plant available water in each season was 104 mm, 91 mm, 28 mm and 27 mm respectively. Rainfall 30 days prior to flowering (approximating the critical period for yield determination) in each year was 8, 6, 14, 190 mm respectively. We only observed a yield benefit in long-cycle treatments in 2011 and 2012 seasons where there was (i) soil water stored at depth (ii) little rain during the critical period. The higher yield of long-cycle treatments could be attributed to greater deep soil water extraction (<1.0 m), dry-matter production and grain number. In 2015, there was little rain during the critical period, no water stored at depth and no difference between treatments. In 2016, high in-crop rainfall filled the soil profile, but high rainfall during the critical period removed crop reliance on deep water, and yields were equivalent. A simulation study extended our findings to demonstrate a median yield benefit in long-cycle treatments when the volume of starting soil water was increased. This work reveals environmental conditions that can be used to quantify the frequency of circumstances where long-cycle wheat will provide a yield advantage over current practice.